Investigating the use of electronic communication and its impact on faculty staff members at a selected university of technology in South Africa - Sallie, Amiena (Cape Peninsula University of Technology, 2019)
The Fourth Industrial Revolution has entrenched the use of communication technologies in the workplace owing to their advantages. However, these same technologies can also present challenges for organisations, especially when employees become too dependent on them, for example, using emails as a sole form of communication. Consequently, this impacts staff interaction, their interpersonal communication, as well as staff cohesion negatively. The main objective of this research study was to establish if faculty staff rely excessively on email communication, resulting in reduced interpersonal communication, staff cohesion, and staff interaction. The researcher used an interpretive phenomenological quantitative research approach in a case study at the Faculty of Business and Management Sciences at UoT X with the aim to understand participants’ email experiences. The sample frame comprised 438 staff members, while the study adopted a non-probability sampling method. The findings revealed that a majority of the employees rely on electronic communication to communicate important information to other staff members in spite of the fact that they did not receive any formal training to use email in a professional business environment. Moreover, the research found that over-reliance on email communication impacted negatively on relationships amongst faculty staff, whilst poor interpersonal communication was a major cause of conflict and misunderstandings, as shown in the literature. Faculty staff should be encouraged to interact with their colleagues on a face-to-face basis, and should only resort to using electronic communication in urgent contexts. Staff relations are built and strengthened by sharing experiences, interacting both formally and informally, resolving disagreements, and encouraging interpersonal dialogue, diversity and tolerance through interactions. Furthermore, faculties should create social environments such as off-campus research retreats, university sports events, conferences, recreational tours, and subject clusters to aid sharing experiences, and staff cohesion.
Thesis (MTech (Business Administration))--Cape Peninsula University of Technology, 2019
Keywords: Electronic communication; interpersonal communication; over-reliance; social cohesion; staff interaction; Universities of Technology